Histopathology of hepatitis C in children, a systematic review: implications for treatment. Issue 10 (3rd October 2015) - Indolfi, Giuseppe; Guido, Maria; Azzari, Chiara; Resti, Massimo
Abstract : Chronic hepatitis C in children is usually considered a clinically mild and slowly progressive disease. Few pediatric studies focused on histopathology of children with hepatitis C are available. Those available show, overall, a wide spectrum of findings ranging from normal liver to cirrhosis and hepatocellular carcinoma. The present systematic review provides a comprehensive overview of the studies that explored histopathology in children with hepatitis C. Factors affecting the presence and the degree of necroinflammation, fibrosis and steatosis and the risk of progression to advanced liver disease were extensively evaluated. Insights on the possible role of histopathology findings in the decision-making process of whether or not to treat children with hepatitis C are provided.